Ceramic production in the American Southwest - Mills, Barbara J., 1955-; Crown, Patricia L. (University of Arizona Press, 1995)
Southwestern ceramics have always been admired for their variety and aesthetic beauty. Although ceramics are most often used for placing the peoples who produced them in time, they can also provide important clues to past economic organization. This volume covers nearly one thousand years of southwestern prehistory and history, focusing on ceramic production in a number of environmental and economic contexts. It brings together the best of current research to illustrate the variation in the organization of production evident in this single geographic area.